Personality traits and their clinical associations in trichotillomania and skin picking disorder - Jon E. Grant; Samuel R. Chamberlain (BMC Psychiatry, 2021)
Abstract Background Despite being discussed in the psychiatric literature for decades, very little is known about personality features associated with trichotillomania and skin picking disorder (known as body focused repetitive behavior disorders, BFRBs); and the contribution of personality traits to their clinical presentations. Aim The present study assessed personality traits in a large and well-characterized sample of adults with either trichotillomania or skin picking disorder or both. Methods Adults (n = 98, aged 18–65 years), with trichotillomania (n = 37), skin picking disorder (n = 32), both trichotillomania and skin picking disorder (n = 10), and controls (n = 19) were enrolled. Participants completed self-report questionnaires to quantify personality (NEO Personality Inventory), as well as extent/severity of picking/pulling symptoms, mood and anxiety, impulsive and perfectionistic tendencies, and neurocognitive functioning. Group differences were characterized and correlations with other measures were examined. Results In comparison to controls, BFRBs had elevated neuroticism scores (p < 0.001), lower extraversion scores (p = 0.023), and lower conscientiousness scores (p = 0.007). Neuroticism was significantly related to both hair pulling (r = 0.24, p < 0.001) and skin picking severity (r = 0.48, p < 0.001), as well as elevated perceived stress, worse anxiety and depressive symptoms, and poorer quality of life. Introversion (i.e. lower extraversion) was significantly associated with worse picking severity, higher perceived stress, and higher depression. Lack of conscientiousness was significantly associated with more depression, impulsivity, and perceived stress. Discussion Personality traits of neuroticism, introversion, and lack of conscientiousness are heightened in individuals with BFRBs and show strong associations with a number of clinically relevant features of illness. The holistic understanding and treatment of these disorders is likely to require consideration of dimensional traits such as these.